Prevalence of Orthopedic Problems in Medical Staff in KSA - Murad, Manal abdulaziz; Alabdali, Ahmed Abdulilah; Abousada, Hoda Jehad; Riyadh Tawfeeq AlMalki,; Alanoud Abdullah Alharbi,; Abdulbari Hamoud Albalawi,; Ahmed Abdulqader Alzahrani,; Jassim Mubarak Aljassim, (International Journal of Innovative Research in Medical Science, 2020)
Among most Medical staff the orthopaedic complaint is very common and, in this research, we focused on the overall Prevalence of orthopaedic disorders among Medical workers, orthopaedic conditions differences between genders and educational levels. Then we overviewed the rates of orthopaedic diseases in different age groups in the general population. These study participants were Medical workers from Saudi Arabia and the results may not be applied to different sittings due to differences in facilities and work conditions.